Parents' Knowledge and Skills in Feeding, Children's Response to Feeding on the Nutritional Status of Toddlers with Malnutrition Problems - Reni Nurhidayah; Dhita Kurnia Sari; Prima Dewi Kusumawati; Betharia Mardiyani; Asmaul Khusna (Universitas STRADA Indonesia, 2023)
Malnutrition, notably stunting, significantly impacts children's health and development, particularly during the first 1000 days of life. The prevalence of stunting in Indonesia is notably high, affecting approximately 30% of children under five in 2019, with Kediri Regency reporting a prevalence rate of 10.23% in 2022. The aim of this research is to analyze the influence of parental knowledge and skills in improving nutritional status as well as children's responses to feeding on the nutritional status of children with malnutrition problems. The research design used in this research is a pre-experimental one group pre-test post-test design. The sampling technique was total sampling with respondents in this study being 22 underprivileged families with toddlers who had nutritional problems and stunting in the Gempolan Village area. The problem of malnutrition in toddlers is quite high with an average Z Score of -2.42 (BB/U), -2.46 (TB/U), and -1.53 (BB/TB). Pre-test data on parents' knowledge and ability to fulfill children's nutrition shows that 68% have fairly good knowledge and skills and only 9% have good knowledge and skills. In this study, 50% of respondents had a fairly good response to feeding. The data highlights a significant problem of malnutrition in toddlers, characterized by low Z-Scores indicating undernutrition and growth stunting. These low Z-Scores pose substantial health risks, including compromised growth, weakened immunity, and potential long-term health issues. Parental knowledge and skills in nutrition are crucial, with most parents having reasonable knowledge levels. However, feeding problems persist, contributing to food rejection by children, exacerbating malnutrition.